Understanding Loneliness in Older Adults During the Pandemic: Predictors and Questionnaire Validation - Rahela Orlandini; Linda Lušić Kalcina; Vesna Antičević (Diseases)
Background/Objectives: The COVID-19 pandemic is behind us, but the experiences gained during its course can serve as a framework for preventive actions in future crises. The main objectives were to examine the predictors of loneliness in older adults during the pandemic and to explore the mediating effects of emotional stability between pandemic-specific stressors and loneliness. To achieve the set objectives, we developed a questionnaire to measure pandemic-specific stressors in older adults. Methods: A cross-sectional research design was used. A total of 578 participants of both genders (38.9% male, 61.1% female) aged 65 and above (M = 74.09, SD = 6.72) participated in this study. The self-reported measures used included the following: The Ten-Item Personality Inventory, The Revised Loneliness Scale, The Clinical Outcomes in Routine Evaluation, and The Pandemic-Specific Stressors Questionnaire for Older Adults. Results: Using exploratory factor analysis, two factors were extracted, providing evidence of face and convergent validity, together explaining 71.3% of the variance. The results of the confirmatory factor analysis indicated a good model fit. Hierarchical regression analysis indicated the greatest contribution of the psychological factors to loneliness in older adults during the pandemic, while marital status and pandemic-specific stressors had a minor but still significant impact. Mediation analysis revealed that emotional stability mediated the association between social distancing experiences and loneliness. Conclusions: In future global pandemics, it is necessary to pay full attention to psychological factors to preserve the mental health of older people. The newly-constructed questionnaire identifies pandemic-specific stressors in older adults, aiding their mitigation and easing recovery from the pandemic crisis.